Globalización: Las tecnologías de la información como reto actual de los negocios (Globalization: Technology information as a business challenge) - Saucedo Elizondo, Edward Antonio; Blanco Jiménez, Mónica; Barragán Codina, José Nicolás (Facultad de Contaduría Pública y Administración U.A.N.L., 2014)
Abstract: This article presents the reasons why globalization has not only become the most recurrent theme of social scientists in the department issues and matters of political debate, but commonplace in the media which has passed into everyday language and family conversations. Aguilar (2002) says that globalization, as God, is omnipresent and omniscient somehow, since it would seem to explain everything that happens in the world, also over powerfully, because of its defenders say, nothing can be opposed to the force of globalization and the contrary it is a new way of life for humanity as a whole is imposed everywhere with the forcefulness of destiny. Globalization appears in our society with an overwhelming force, as an ongoing process that cannot be stopped, however, that focusing resources properly can counteract nations to dominate and get significant benefits for each country in different sectors. This paper briefly describes some benefits that globalization brings like the process of innovation and the use of Information Technology and the positives effects on nations simply do accept it in their business.